After Art - Joselit, David (Book collections on Project MUSE., 2012)
Art as we know it is dramatically changing, but popular and critical responses lag behind. In this trenchant illustrated essay, David Joselit describes how art and architecture are being transformed in the age of Google. Under the dual pressures of digital technology, which allows images to be reformatted and disseminated effortlessly, and the exponential acceleration of cultural exchange enabled by globalization, artists and architects are emphasizing networks as never before. Some of the most interesting contemporary work in both fields is now based on visualizing patterns of dissemination.